Wilkie Collins: The Complete Fiction, by Stephen Knight - Vargün, Ahmet Can (My University, 2024)
Stephen Knight’s monograph, Wilkie Collins: The Complete Fiction (2023, Routledge) is a detailed study of Wilkie Collins’ life and career as a complex and accomplished author; ultimately, it presents a call for more scholarly attention and interest in his works. The study engages Collins’ complete fiction by grounding his texts in historical and biographical context. Knight offers extensive background about events, politics, anecdotes, and interactions as Collins built his writing career. Moreover, the study presents details about Collins’ life, his engagement with the publishing industry, and his interaction with other authors at the time. By this approach, the book explores Collins’ literary production considering the influence of consumption, and the criticism of his works to better understand and position him as a complex and successful author. Knight’s monograph also offers historical context and recent scholarly criticism of Collins studies. While this exploration sheds light on Collins’ development as a successful author, producer of novelty, and a political voice, the study repeats the argument that Collins’ works have not received the scholarly attention they deserve.
Keywords: Wilkie Collins; Stephen Knight; 19th century Britain